Sealant for organic EL display element and organic EL display element
By using a specific range of polyisobutylene-based polymers and (meth)acryloyl monomers in the photocurable resin sealant, combining water-absorbing fillers and photo-radical polymerization initiators, the photocurable resin sealing in the prior art is solved by using a specific range of polyisobutylene-based polymerization. The solvent dilution and uneven shape of the agent achieve efficient barrier properties and adhesiveness, and are suitable for sealing of organic EL display elements and quantum dot devices.
Patent Information
- Application Number
- CN202210169452.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-02-14
- Filing Date
- 2018-02-08
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2038-02-08
AI Technical Summary
The existing photocurable resin sealant has solvent dilution problems during the coating and curing process, resulting in insufficient barrier properties and adhesion of organic EL display elements and quantum dot devices, and is prone to damage to the components and uneven shapes.
The polyisobutylene-based polymer with a weight average molecular weight between 50 million and 100,000, monomers with an alicyclic backbone and (meth)acryloyl group, and a water-absorbing filler are used to generate a photoradical polymerization initiator and augmentation filler. The bonding of the adhesive forms a solvent-free photocurable resin composition, optimizes its viscosity and filler content to improve coating and barrier properties.
A photocurable resin composition with excellent storage stability, coating properties, adhesion and barrier properties is achieved. It is used to prepare sealants for organic EL display elements and quantum dot equipment, avoiding damage and shape in the drying process. The problem of unevenness improves the long life and performance of the component.
Smart Images

Figure QLYQS_1 
Figure BDA0003516930860000031 
Figure BDA0003516930860000191
Abstract
Description
[0001] This application is a divisional application. The filing date of the parent application is February 8, 2018. The international application number is PCT / JP2018 / 004353. The application number entering the Chinese national phase is 201880004317.9. The name of the invention is photocurable resin composition, sealant for organic EL display element, organic EL display element, sealant for quantum dot device, and quantum dot device. Technical Field
[0002] The present invention relates to a photocurable resin composition having excellent storage stability, coating properties, adhesion and barrier properties. In addition, the present invention relates to a sealant for an organic EL display element and a sealant for a quantum dot device comprising the photocurable resin composition, an organic EL display element manufactured using the sealant for an organic EL display element, and a quantum dot device manufactured using the sealant for a quantum dot device. Background Art
[0003] An organic electroluminescent (hereinafter also referred to as "organic EL") display element has a laminated structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. While electrons are injected into the organic light-emitting material layer from one electrode, holes are injected into the organic light-emitting material layer from the other electrode, whereby electrons and holes are combined in the organic light-emitting material layer to emit light. As such, an organic EL display element emits light by itself, and therefore has the following advantages over a liquid crystal display element that requires a backlight: good visual recognition, thinness, and DC low voltage drive.
[0004] The organic light-emitting material layer and electrode constituting the organic EL display element have the problem that their characteristics are easily degraded by moisture, oxygen, etc. Therefore, in order to obtain a practical organic EL display element, it is necessary to isolate the organic light-emitting material layer and the electrode from the atmosphere to achieve a long life. As a method of isolating the organic light-emitting material layer and the electrode from the atmosphere, for example, Patent Document 1 discloses the following method: covering the top of the stacked body with the organic light-emitting material layer arranged on the substrate with a sealing component, and surrounding it with a sealing wall formed by a sealant (peripheral sealant). For such a peripheral sealant, high barrier properties that isolate moisture, oxygen, etc. are required; coating properties when applied on the substrate by dispensing, etc.; curing properties when the substrate and the sealing component are pasted and cured by light irradiation or heating; and adhesion and toughness to bond and fix the substrate and the sealing component, and maintain the seal without defects caused by peeling and cracking.
[0005] Patent document 2 discloses a composition, wherein, as a curable resin composition that can be used as a peripheral sealant, it contains a high molecular weight polyisobutylene resin and a multifunctional (meth) acrylate monomer. However, the previous sealant disclosed in Patent document 2 has the following problems: solvent dilution is required during coating, and the organic EL display element is easily damaged by the solvent itself and the heating in the drying process for removing the solvent after coating. In addition, in the drying process, the shape of the sealant tends to become uneven, making it difficult to use as a peripheral sealant for sealing the periphery of a laminate having an organic light-emitting material layer.
[0006] In addition, in recent years, quantum dot devices that utilize the quantum size effect have attracted attention. The quantum size effect refers to the following phenomenon: if the semiconductor crystal is reduced to a nano-sized particle, the electron is confined in the tiny area and cannot move freely, so the energy that the electron can achieve is quantized. In this way, the particles in which the electrons are confined in a tiny area are called quantum dots. By adjusting the particle size of the quantum dots, the band gap is changed, so that the wavelength of light absorption can be controlled. As a quantum dot device that utilizes this quantum size effect, for example, a liquid crystal display element that achieves excellent color display capabilities by configuring a wavelength conversion sheet using quantum dots on the backlight has been developed. Since the characteristics of quantum dots are easily degraded by moisture, oxygen, etc., this wavelength conversion sheet needs to isolate the quantum dots from moisture, etc. For example, Patent Document 3 discloses a wavelength conversion sheet formed by stacking a phosphor layer using quantum dots and a barrier film. However, in the previous sealing using a barrier film, it is difficult to fully isolate the quantum dots from moisture, etc.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2007-59094
[0010] Patent Document 2: Japanese Patent Application No. 2011-526629
[0011] Patent Document 3: International Publication No. 2015-037733 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The object of the present invention is to provide a photocurable resin composition having excellent storage stability, coating properties, adhesion and barrier properties. In addition, the object of the present invention is to provide a sealant for an organic EL display element and a sealant for a quantum dot device comprising the photocurable resin composition, an organic EL display element manufactured using the sealant for an organic EL display element, and a quantum dot device manufactured using the sealant for a quantum dot device.
[0014] Methods for solving problems
[0015] The present invention is a photocurable resin composition comprising: a polymer having a repeating unit represented by the following formula (1) in its main chain and a weight average molecular weight of 5000 to 100,000, a monomer having an alicyclic skeleton and a (meth)acryloyl group, a photoradical polymerization initiator, and a water-absorbing filler. The photocurable resin composition does not contain a solvent, and the content of the monomer having an alicyclic skeleton and a (meth)acryloyl group is 30 parts by weight to 90 parts by weight, and the content of the water-absorbing filler is 5 parts by weight to 200 parts by weight, based on 100 parts by weight of the total of the polymer having a repeating unit represented by the following formula (1) in its main chain and a weight average molecular weight of 5000 to 100,000 and the monomer having an alicyclic skeleton and a (meth)acryloyl group, and the viscosity measured using an E-type viscometer at 25° C. and 2.5 rpm is 1 Pa·s to 1000 Pa·s.
[0016] [Chemistry 1]
[0017]
[0018] Hereinafter, the present invention will be described in detail.
[0019] The present inventors have studied: by adding a low molecular weight polyisobutylene polymer as a resin component to a (meth) acrylic monomer or an epoxy monomer, and then mixing it with a water-absorbing filler, a sealant with excellent coating properties and excellent barrier properties can be prepared without using an organic solvent. However, the resulting sealant has the following problems: it is easy to phase separate, has poor storage stability, or the polyisobutylene polymer oozes out during a heat resistance test of the cured product, resulting in reduced adhesion. Therefore, the present inventors have studied: a polyisobutylene polymer with a weight average molecular weight in a specific range, a monomer having an alicyclic skeleton and a (meth) acryloyl group, and a water-absorbing filler are mixed in a manner to achieve a specific content ratio, and the viscosity is adjusted to a specific range. As a result, it was found that a photocurable resin composition with excellent storage stability, coating properties, adhesion and barrier properties can be obtained, thereby completing the present invention.
[0020] In addition, in this specification, the said "(meth)acryloyl group" means an acryloyl group or a methacryloyl group.
[0021] The photocurable resin composition of the present invention contains a polymer having a repeating unit represented by the above formula (1) in the main chain and having a weight average molecular weight of 5,000 to 100,000 (hereinafter also referred to as "polyisobutylene polymer of the present invention").
[0022] The polyisobutylene polymer of the present invention has a hydrophobic and bulky skeleton including a repeating unit represented by the above formula (1) in the main chain, and thus has a large excluded volume despite being amorphous, and the photocurable resin composition of the present invention has excellent barrier properties.
[0023] The polyisobutylene polymer of the present invention may have other structural units in addition to the repeating unit represented by the above formula (1). That is, as long as the polyisobutylene polymer of the present invention has the repeating unit represented by the above formula (1), it may have a reactive functional group such as a (meth)acryloyl group as the above other structural unit at the terminal, or it may be a copolymer having the above other structural unit as a repeating unit in addition to the repeating unit represented by the above formula (1).
[0024] When having the above other structural units, the polyisobutylene polymer of the present invention preferably contains 80% by weight or more, more preferably 90% by weight or more, of the repeating unit represented by the above formula (1) from the viewpoint of barrier properties.
[0025] The lower limit of the weight average molecular weight of the polyisobutylene polymer of the present invention is 5000 and the upper limit is 100,000. By making the weight average molecular weight of the polyisobutylene polymer of the present invention within this range, the compatibility with the monomer having an alicyclic skeleton and a (meth) acryloyl group described later becomes excellent. Therefore, the storage stability of the obtained photocurable resin composition is excellent, and the polyisobutylene polymer of the present invention is suppressed from oozing out from the cured product, and the adhesion also becomes excellent. The preferred lower limit of the weight average molecular weight of the polyisobutylene polymer of the present invention is 20,000, the preferred upper limit is 80,000, the more preferred lower limit is 30,000, and the more preferred upper limit is 60,000.
[0026] It should be noted that, in this specification, the above-mentioned weight average molecular weight is measured by gel permeation chromatography (GPC), and the value obtained by polystyrene conversion. As a column when using GPC to measure the weight average molecular weight based on polystyrene conversion, for example Shodex LF-804 (Showa Denko Co., Ltd. system) etc. can be listed. In addition, as the solvent used in GPC, tetrahydrofuran etc. can be listed.
[0027] Examples of commercially available products of the polyisobutylene polymer of the present invention include polyisobutylene polymers manufactured by KANEKA Corporation, polyisobutylene polymers manufactured by JX Nippon Mining & Energy Corporation, and polyisobutylene polymers manufactured by BASF Corporation.
[0028] Examples of the polyisobutylene polymer manufactured by KANEKA include EPION 200A (weight average molecular weight: 6,900), EPION 400A (weight average molecular weight: 13,000), and EPION 600A (weight average molecular weight: 19,000).
[0029] Examples of the polyisobutylene polymer manufactured by JX Nippon Oil & Energy Corporation include Tetrax 3T (weight average molecular weight of 49,000), Tetrax 4T (weight average molecular weight of 59,000), Tetrax 5T (weight average molecular weight of 69,000), Tetrax 6T (weight average molecular weight of 80,000), HYMOL 4H (weight average molecular weight of 5,000 to 100,000), HYMOL 5H (weight average molecular weight of 5,000 to 100,000), HYMOL 5.5H (weight average molecular weight of 5,000 to 100,000), and HYMOL 6H (weight average molecular weight of 5,000 to 100,000).
[0030] Examples of the polyisobutylene polymer manufactured by BASF include Oppanol B10 (weight average molecular weight: 36,000), Oppanol B11 (weight average molecular weight: 46,000), Oppanol B12 (weight average molecular weight: 51,000), Oppanol B13 (weight average molecular weight: 60,000), Oppanol B14 (weight average molecular weight: 65,000), and Oppanol B15 (weight average molecular weight: 75,000).
[0031] The polyisobutylene polymer of the present invention may be used alone or in combination of two or more.
[0032] The photocurable resin composition of the present invention may contain other polymers in addition to the polyisobutylene polymer of the present invention within a range not impairing the object of the present invention.
[0033] Examples of the other polymers include polybutene polymers, polyisoprene polymers, hydrogenated polyisoprene polymers, polybutadiene polymers, hydrogenated polybutadiene polymers, polyisobutylene polymers having a weight average molecular weight exceeding 100,000, and copolymers or modified products thereof. Among them, polyisobutylene polymers having a weight average molecular weight exceeding 100,000 are preferred from the viewpoint of barrier properties, and polybutadiene polymers having a (meth)acryloyl group at the terminal and polyisoprene polymers having a (meth)acryloyl group at the terminal are preferred from the viewpoint of reactivity.
[0034] These other polymers may be used alone or in combination of two or more.
[0035] Examples of commercially available products of the polyisobutylene polymer having a weight average molecular weight exceeding 100,000 include Oppanol B30SF, Oppanol B50, Oppanol B50SF, Oppanol B80, Oppanol B100, Oppanol B150, and Oppanol B200 (all manufactured by BASF).
[0036] Examples of commercially available products of the polybutadiene polymer having a (meth)acryloyl group at the terminal include CN307 and CN9014NS (both manufactured by ARKEMA), BAC-45 (manufactured by Osaka Organic Chemical Industry Co., Ltd.), TE-2000, and TEAI-1000 (both manufactured by Nippon Soda Co., Ltd.).
[0037] As a commercially available product among the polyisoprene-based polymers having a (meth)acryloyl group at the terminal, for example, Kuraprene UC-102M (manufactured by KURARAY CO., LTD.) etc. can be mentioned.
[0038] The photocurable resin composition of the present invention contains a monomer having an alicyclic skeleton and a (meth)acryloyl group (hereinafter also referred to as “the (meth)acrylic monomer of the present invention”).
[0039] The (meth)acrylic monomer of the present invention has excellent compatibility with the polyisobutylene polymer of the present invention. Therefore, by containing the (meth)acrylic monomer of the present invention, the polyisobutylene polymer of the present invention is suppressed from bleeding out from the cured product, and the resulting photocurable resin composition has excellent adhesion and excellent storage stability.
[0040] In addition, in this specification, the said "(meth)acrylic acid" means acrylic acid or methacrylic acid.
[0041] From the viewpoint of barrier properties and the like, the alicyclic skeleton contained in the (meth)acrylic monomer of the present invention is preferably a bridged alicyclic skeleton.
[0042] Furthermore, from the viewpoint of barrier properties, the (meth)acrylic monomer of the present invention preferably has a methacryloyl group as the (meth)acryloyl group.
[0043] The preferred upper limit of the molecular weight of the (meth)acrylic monomer of the present invention is 1000. By setting the molecular weight of the (meth)acrylic monomer of the present invention to 1000 or less, the photocurability of the obtained photocurable resin composition becomes more excellent. The more preferred upper limit of the molecular weight of the (meth)acrylic monomer of the present invention is 500.
[0044] The preferred lower limit of the molecular weight of the (meth)acrylic monomer of the present invention is not particularly limited, but the substantial lower limit is 150.
[0045] Specific examples of the (meth)acrylic monomer of the present invention include bornyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, norbornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 2-(meth)acryloyloxy-2-methyladamantane, 2-(meth)acryloyloxy-2-methyladamantane, and 2-(meth)acryloyloxy-2-methyladamantane. Ethyladamantane, 2-(meth)acryloyloxy-2-isopropyladamantane, 1-(meth)acryloyloxy-3,5-dimethyladamantane, 1-adamantane methanol (meth)acrylate, 1-adamantane ethanol (meth)acrylate, 3,5-dimethyl-1-methanoladamantane (meth)acrylate, dicyclopentadienyl dimethanol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, 1,3-adamantanediol di(meth)acrylate, 1,3,5-adamantantriol tri(meth)acrylate, and the like. Among them, at least one selected from isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentadienyl dimethanol di(meth)acrylate and trimethylcyclohexyl (meth)acrylate is preferred, and at least one selected from isobornyl methacrylate, dicyclopentanyl methacrylate, 1-adamantyl methacrylate, dicyclopentanyl dimethanol dimethacrylate and trimethylcyclohexyl methacrylate is more preferred.
[0046] These (meth)acrylic monomers may be used alone or in combination of two or more.
[0047] In the total of 100 parts by weight of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention, the lower limit of the content of the (meth) acrylic monomer of the present invention is 30 parts by weight and the upper limit is 90 parts by weight. By making the content of the (meth) acrylic monomer of the present invention more than 30 parts by weight, the coating property, curability and adhesion of the obtained photocurable resin composition become excellent. By making the content of the (meth) acrylic monomer of the present invention less than 90 parts by weight, the barrier property of the obtained photocurable resin composition becomes excellent. The preferred lower limit of the content of the (meth) acrylic monomer of the present invention is 35 parts by weight, the preferred upper limit is 80 parts by weight, the more preferred lower limit is 40 parts by weight, and the more preferred upper limit is 70 parts by weight.
[0048] The photocurable resin composition of the present invention may contain other polymerizable monomers in addition to the (meth)acrylic monomer of the present invention in a range that does not impair compatibility in order to further improve adhesiveness and the like.
[0049] As the other polymerizable monomer, other (meth)acrylic monomers other than the (meth)acrylic monomer of the present invention are preferred.
[0050] Examples of the other (meth)acrylic monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, and tert-butyl (meth)acrylate. ) stearyl acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate alcohol (meth)acrylate, phenoxy polyethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, imide (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl Phosphate, glycidyl (meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide added bisphenol A di(meth)acrylate, propylene oxide added bisphenol A di(meth)acrylate, ethylene oxide added bisphenol F di(meth)acrylate, (meth)acrylate 2-hydroxy-3-(meth)acryloyloxypropyl, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutane diol Ethylenediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide added trimethylolpropane tri(meth)acrylate, propylene oxide added trimethylolpropane tri(meth)acrylate, caprolactone modified trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc.
[0051] The above-mentioned other polymerizable monomers may be used alone or in combination of two or more.
[0052] The photocurable resin composition of the present invention contains a photoradical polymerization initiator.
[0053] Examples of the photoradical polymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, benzil, and thioxanthone.
[0054] These photoradical polymerization initiators may be used alone or in combination of two or more.
[0055] As what is commercially available among the said radical photopolymerization initiator, the radical photopolymerization initiator manufactured by BASF Corporation, the radical photopolymerization initiator manufactured by Tokyo Chemical Industry Co., Ltd., etc. are mentioned, for example.
[0056] Examples of the photoradical polymerization initiator manufactured by BASF include IRGACURE 184, IRGACURE 369, IRGACURE 379, IRGACURE 651, IRGACURE 819, IRGACURE 907, IRGACURE 2959, IRGACURE OXE01, and LUCIRIN TPO.
[0057] Examples of the photoradical polymerization initiator manufactured by Tokyo Chemical Industry Co., Ltd. include benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether.
[0058] The preferred lower limit of the content of the above-mentioned free radical polymerization initiator is 0.1 parts by weight and the preferred upper limit is 10 parts by weight relative to the total of 100 parts by weight of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By making the content of the above-mentioned free radical polymerization initiator within this range, the curability, storage stability and barrier properties of the obtained photocurable resin composition become more excellent. The more preferred lower limit of the content of the above-mentioned free radical polymerization initiator is 0.2 parts by weight, the more preferred upper limit is 5 parts by weight, the further preferred lower limit is 0.5 parts by weight, and the further preferred upper limit is 3 parts by weight.
[0059] The photocurable resin composition of the present invention contains a water-absorbing filler.
[0060] By containing the water-absorbing filler, the photocurable resin composition of the present invention has excellent barrier properties.
[0061] The preferred lower limit of the average primary particle size of the water-absorbing filler is 0.5 μm, and the preferred upper limit is 5 μm. By setting the average primary particle size of the water-absorbing filler to this range, the resulting photocurable resin composition can suppress panel peeling when used as a sealant for an organic EL display element, and the barrier properties are further improved. The more preferred lower limit of the average primary particle size of the water-absorbing filler is 0.8 μm, and the more preferred upper limit is 3 μm.
[0062] In addition, in this specification, the said "average primary particle diameter" can be measured using a dynamic light scattering particle size measuring apparatus (made by Otsuka Electronics Co., Ltd., "ELSZ-1000S") etc.
[0063] The preferred lower limit of the specific gravity of the water-absorbing filler is 1.5 g / cm 3 The upper limit is preferably 3.3 g / cm 3 By setting the specific gravity of the water-absorbing filler to be within this range, the resulting photocurable resin composition can suppress panel peeling when used as a sealant for an organic EL display element and has better barrier properties. The more preferred lower limit of the specific gravity of the water-absorbing filler is 2.0 g / cm 3 The upper limit is more preferably 3.0 g / cm 3 .
[0064] In addition, the said "specific gravity" means the value measured by the method based on JIS Z8807.
[0065] The preferred lower limit of the average specific surface area of the water-absorbing filler is 5 m 2 / g, the upper limit is preferably 20m2 / g. By setting the average specific surface area of the water-absorbing filler to this range, the resulting photocurable resin composition can suppress panel peeling when used as a sealant for an organic EL display element and has better barrier properties. The more preferred lower limit of the average specific surface area of the water-absorbing filler is 10 m 2 / g, and the upper limit is more preferably 18m 2 / g.
[0066] The “average specific surface area of the water-absorbing filler” can be measured by a BET method using nitrogen gas using a specific surface area measuring device (for example, “ASAP-2000” manufactured by Shimadzu Corporation).
[0067] The preferred lower limit of the total surface area of the water-absorbing filler per 100 g of the photocurable resin composition of the present invention is 10 m 2 、The preferred upper limit is 100m 2 By making the total surface area of the water-absorbing filler within this range, the resulting photocurable resin composition can suppress panel peeling when used as a sealant for an organic EL display element and has better barrier properties. The more preferred lower limit of the total surface area of the water-absorbing filler is 20 m 2 The upper limit is preferably 80m 2 .
[0068] It should be noted that the “total surface area of the water-absorbing filler” can be calculated from the content of the water-absorbing filler and the average specific surface area of the water-absorbing filler.
[0069] The preferred lower limit of the water absorption rate of the water-absorbing filler is 10% by weight. When the water absorption rate of the water-absorbing filler is 10% by weight or more, the barrier property of the obtained photocurable resin composition becomes more excellent. The more preferred lower limit of the water absorption rate of the water-absorbing filler is 20% by weight.
[0070] In addition, the preferred upper limit of the water absorption rate of the water-absorbing filler is not particularly limited, but the substantial upper limit is 65% by weight.
[0071] It should be noted that the above-mentioned "water absorption rate" refers to the weight change rate when the high temperature and high humidity test is carried out in an atmosphere of temperature 85°C and humidity 85% for 24 hours. Specifically, the weight before the high temperature and high humidity test (85°C-85%, 24 hours) is recorded as W1, and the weight after the high temperature and high humidity test is recorded as W2, and it is calculated by the following formula (I).
[0072] Water absorption (weight %) = ((W2-W1) / W1) × 100 (I)
[0073] Examples of materials constituting the water-absorbing filler include alkaline earth metal oxides such as calcium oxide, strontium oxide, and barium oxide; magnesium oxide, and molecular sieves, etc. Among them, alkaline earth metal oxides are preferred, and calcium oxide is more preferred, from the viewpoint of water absorption.
[0074] These water-absorbing fillers may be used alone or in combination of two or more.
[0075] The lower limit of the content of the water-absorbing filler is 5 parts by weight and the upper limit is 200 parts by weight relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By setting the content of the water-absorbing filler within this range, the photocurable resin composition obtained has excellent effects of achieving both barrier properties and adhesive properties. The preferred lower limit of the content of the water-absorbing filler is 10 parts by weight, the preferred upper limit is 100 parts by weight, the more preferred lower limit is 15 parts by weight, the more preferred upper limit is 60 parts by weight, and the further preferred upper limit is 50 parts by weight.
[0076] The photocurable resin composition of the present invention may contain fillers other than the water-absorbing filler in order to further improve barrier properties, coating properties, and the like.
[0077] Examples of the other fillers include inorganic fillers such as talc, silica, and alumina, and organic fillers such as polyester microparticles, polyurethane microparticles, vinyl polymer microparticles, and acrylic polymer microparticles, etc. Among them, it is preferred to contain talc and / or silica, and it is more preferred to contain talc and / or fumed silica.
[0078] These other fillers may be used alone or in combination of two or more.
[0079] When talc is used as the other filler, the lower limit of the average primary particle size of the talc is preferably 5 μm, the upper limit is preferably 50 μm, and the upper limit is more preferably 12 μm from the viewpoint of barrier properties and coating properties.
[0080] When silica is used as the other filler, the average primary particle size of silica is preferably 7 nm in the lower limit and 10 μm in the upper limit, more preferably 10 nm in the lower limit and 1 μm in the upper limit, from the viewpoint of coating properties.
[0081] Examples of commercially available products of the talc include MICRO ACE P-4, MICRO ACE P-6, and MICRO ACE P-8 (all manufactured by Nippon Talc Co., Ltd.).
[0082] As a commercial item among the said silica, AEROSIL200, AEROSIL300, AEROSIL380 (all are manufactured by NIPPON AEROSIL CO., LTD.), etc. are mentioned, for example.
[0083] The content of the other fillers may be appropriately adjusted according to the viscosity of the photocurable resin composition to be obtained.
[0084] When talc is used as the other filler, the preferred lower limit of the content of the talc is 5 parts by weight and the preferred upper limit is 50 parts by weight relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By setting the content of the talc within this range, the photocurable resin composition obtained has a better effect of achieving both adhesion and barrier properties. The more preferred lower limit of the content of the talc is 10 parts by weight and the more preferred upper limit is 40 parts by weight.
[0085] When silica is used as the other filler, the preferred lower limit of the content of the silica is 0.1 parts by weight and the preferred upper limit is 30 parts by weight relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By setting the content of the silica to be within this range, the photocurable resin composition obtained has a better effect of achieving both coating properties and barrier properties. The more preferred lower limit of the content of the silica is 1 part by weight and the more preferred upper limit is 20 parts by weight.
[0086] The total content of the water-absorbing filler and the other fillers is preferably 100 parts by weight or less relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth)acrylic monomer of the present invention. By setting the total content of the water-absorbing filler and the other fillers to be within this range, the photocurable resin composition obtained has a better effect of achieving both adhesion and barrier properties. The more preferred upper limit of the total content of the water-absorbing filler and the other fillers is 80 parts by weight.
[0087] The photocurable resin composition of the present invention preferably contains a tackifier.
[0088] Examples of the tackifier include terpene resins, modified terpene resins, coumarone resins, indene resins, and petroleum resins.
[0089] Examples of the modified terpene resin include hydrogenated terpene resins, terpene-phenol copolymer resins, and aromatic modified terpene resins.
[0090] Examples of the petroleum resin include alicyclic petroleum resins, non-cyclic aliphatic petroleum resins, aromatic petroleum resins, and aliphatic-aromatic copolymerized petroleum resins.
[0091] Among them, from the viewpoints of compatibility with other components, adhesion and barrier properties of the resulting photocurable resin composition, the above-mentioned tackifier is preferably a petroleum resin, more preferably an alicyclic petroleum resin, an aromatic petroleum resin, or an aliphatic-aromatic copolymer petroleum resin, and particularly preferably an alicyclic petroleum resin.
[0092] These thickeners may be used alone or in combination of two or more.
[0093] Examples of commercially available alicyclic petroleum resins include alicyclic petroleum resins manufactured by ZEON Corporation, alicyclic petroleum resins manufactured by Arakawa Chemical Industries, Ltd., alicyclic petroleum resins manufactured by Idemitsu Kosan Co., Ltd., and alicyclic petroleum resins manufactured by Exxon Mobil Corporation.
[0094] Examples of the alicyclic petroleum resin manufactured by ZEON Corporation of Japan include Quintone 1325 and Quintone 1345.
[0095] Examples of the alicyclic petroleum resin manufactured by Arakawa Chemical Industries, Ltd. include ALCON P-100, ALCON P-125, and ALCON P-140.
[0096] Examples of the alicyclic petroleum resin manufactured by Idemitsu Kosan include IMARV S-100, IMARV S-110, IMARV P-100, IMARV P-125, and IMARV P-140.
[0097] Examples of the alicyclic petroleum resin manufactured by Exxon Mobil Corporation include Escorez 5300 series and 5600 series.
[0098] As a commercially available item among the said aromatic petroleum resin, ENDEX155 (made by EASTMAN CORPORATION) etc. are mentioned, for example.
[0099] Examples of commercially available products of the aliphatic aromatic copolymer petroleum resins include Quintone D100 (manufactured by ZEON Corporation of Japan).
[0100] The preferred lower limit of the content of the tackifier is 1 part by weight and the preferred upper limit is 15 parts by weight relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By setting the content of the tackifier to be within this range, the obtained photocurable resin composition maintains excellent curability and barrier properties, and has better adhesion. The more preferred lower limit of the content of the tackifier is 5 parts by weight and the more preferred upper limit is 10 parts by weight.
[0101] The photocurable resin composition of the present invention may contain a sensitizer. The sensitizer has a function of further improving the polymerization initiation efficiency of the photoradical polymerization initiator and further promoting the curing reaction of the photocurable resin composition of the present invention.
[0102] Examples of the sensitizer include anthracene compounds, thioxanthone compounds, 2,2-dimethoxy-1,2-diphenylethane-1-one, benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4′-bis(dimethylamino)benzophenone, and 4-benzoyl-4′methyldiphenyl sulfide.
[0103] Examples of the anthracene-based compound include 9,10-dibutoxyanthracene and the like.
[0104] Examples of the thioxanthone-based compound include 2,4-diethylthioxanthone and the like.
[0105] These sensitizers may be used alone or in combination of two or more.
[0106] The preferred lower limit of the content of the sensitizer is 0.05 parts by weight and the preferred upper limit is 3 parts by weight relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By making the content of the sensitizer 0.05 parts by weight or more, the sensitization effect can be further exerted. By making the content of the sensitizer 3 parts by weight or less, light can be propagated to a deep part without excessive absorption. The more preferred lower limit of the content of the sensitizer is 0.1 parts by weight and the more preferred upper limit is 1 part by weight.
[0107] The photocurable resin composition of the present invention may contain a silane coupling agent. The silane coupling agent has a function of improving the adhesion between the photocurable resin composition of the present invention and a substrate or the like.
[0108] As the silane coupling agent, a known silane coupling agent that is compatible with the polyolefin polymer of the present invention can be used. Specific examples include 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-ethyl-((triethoxysilylpropoxy)methyl)oxetane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane.
[0109] These silane coupling agents may be used alone or in combination of two or more.
[0110] The preferred lower limit of the content of the silane coupling agent is 0.1 parts by weight and the preferred upper limit is 5 parts by weight relative to 100 parts by weight of the total of the polyisobutylene polymer of the present invention and the (meth) acrylic monomer of the present invention. By setting the content of the silane coupling agent within this range, the obtained photocurable resin composition maintains excellent barrier properties and has better adhesion. The more preferred lower limit of the content of the silane coupling agent is 0.3 parts by weight and the more preferred upper limit is 3 parts by weight.
[0111] The photocurable resin composition of the present invention does not contain a solvent.
[0112] The photocurable resin composition of the present invention has excellent coating properties even without containing the solvent. Therefore, even when used to manufacture organic EL display elements, quantum dot devices, etc., no drying process is required, and damage to elements and devices due to the occurrence of degassing can be suppressed.
[0113] It should be noted that, in the present specification, “containing no solvent” means that the content of the solvent is less than 1000 ppm.
[0114] Furthermore, the photocurable resin composition of the present invention may contain various known additives such as an ultraviolet absorber, a light stabilizer, an antioxidant, and a colorant as necessary within a range not impairing the purpose of the present invention.
[0115] Examples of a method for producing the photocurable resin composition of the present invention include a method of mixing the polyisobutylene polymer of the present invention, the (meth)acrylic monomer of the present invention, a photoradical polymerization initiator, a water-absorbing filler, and additives such as a tackifier and a silane coupling agent using a mixer.
[0116] Examples of the above-mentioned mixer include a homogenizer, a homogeneous mixer, a universal mixer, a planetary mixer, a kneader, a three-roll mill, etc.
[0117] The lower limit of the viscosity of the photocurable resin composition of the present invention measured using an E-type viscometer under the conditions of 25°C and 2.5 rpm is 1 Pa·s, and the upper limit is 1000 Pa·s. By making the above viscosity within this range, the coatability and shape retention of the photocurable resin composition of the present invention become excellent. The preferred lower limit of the above viscosity is 10 Pa·s, the preferred upper limit is 800 Pa·s, more preferably the lower limit is 50 Pa·s, and more preferably the upper limit is 500 Pa·s.
[0118] The photocurable resin composition of the present invention can be suitably used as a sealant for an organic EL display element. The sealant for an organic EL display element containing the photocurable resin composition of the present invention is also one of the present inventions.
[0119] The sealing of the organic EL display element using the sealant for an organic EL display element of the present invention is not to attach a pre-formed sheet-like sealant, but to coat the sealant into a desired shape and then form a sealing portion by curing it. Further, the sealant for an organic EL display element of the present invention can be applied to so-called dam filling sealing.
[0120] As the shape of the sealing portion formed by the sealant for an organic EL display element of the present invention, as long as it can protect the laminate having an organic light-emitting material layer from the influence of external air, there is no particular limitation. It can be a shape that completely covers the laminate, or a sealing wall can be formed around the laminate. Among them, since the sealant for an organic EL display element of the present invention forms this sealing wall, it can be suitably used as a peripheral sealant for an organic EL display element.
[0121] The organic EL display element made using the sealant for an organic EL display element of the present invention is also one of the present inventions.
[0122] In addition, the photocurable resin composition of the present invention can be suitably used as a sealant for a quantum dot device. The sealant for a quantum dot device containing the photocurable resin composition of the present invention is also one of the present inventions.
[0123] The sealing of the quantum dot device using the sealant for a quantum dot device of the present invention is not to attach a pre-formed sheet-like sealant, but to coat the sealant into a desired shape and then form a sealing portion by curing it. Further, the sealant for a quantum dot device of the present invention can be applied to so-called dam filling sealing.
[0124] The shape of the sealing portion formed by the sealant for the quantum dot device of the present invention is not particularly limited as long as it can protect the layer containing the quantum dots from the influence of external air. It can be a shape that completely covers the layer containing the quantum dots, or it can form a sealing wall around the layer containing the quantum dots.
[0125] A quantum dot device made using the sealant for quantum dot devices of the present invention is also one of the present invention. As the quantum dot device of the present invention, it is preferably a display element using quantum dots, and more preferably a liquid crystal display element using quantum dots. When the quantum dot device of the present invention is a display element using quantum dots, the sealant for quantum dot devices of the present invention can be applied to the sealing of a wavelength conversion sheet using quantum dots.
[0126] Effects of the Invention
[0127] According to the present invention, a photocurable resin composition having excellent storage stability, coating properties, adhesion and barrier properties can be provided. In addition, according to the present invention, a sealant for an organic EL display element and a sealant for a quantum dot device comprising the photocurable resin composition, an organic EL display element manufactured using the sealant for an organic EL display element, and a quantum dot device manufactured using the sealant for a quantum dot device can be provided. DETAILED DESCRIPTION
[0128] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0129] (Examples 1 to 17, Comparative Examples 1 to 11)
[0130] According to the mixing ratios described in Tables 1 to 3, each material was stirred and mixed at a stirring speed of 2000 rpm using a stirring mixer (manufactured by THINKY, "AR-250"), and then further kneaded using a three-roll mill (manufactured by NORITAKE, "NR-42A") to prepare the photocurable resin compositions of Examples 1 to 17 and Comparative Examples 1 to 11.
[0131] Tables 1 to 3 show the viscosities of the obtained photocurable resin compositions measured at 25° C. and 2.5 rpm using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., “VISCOMETER TV-22”).
[0132] <Evaluation>
[0133] The following evaluations were performed on each of the photocurable resin compositions obtained in Examples and Comparative Examples. The results are shown in Tables 1 to 3.
[0134] (Storage stability (phase separation))
[0135] Each photocurable resin composition obtained in the embodiment and the comparative example was coated on a glass plate to a thickness of 100 μm using a scraper. After being placed at 25° C. for 10 minutes, the coating film was observed using an optical microscope (magnification 20 times), and the case where no phase separation was observed was recorded as “○”, the case where phase separation was observed was recorded as “△”, and the case where phase separation was observed by visual observation without using an optical microscope was recorded as “×” to evaluate the storage stability.
[0136] (Adhesion)
[0137] For each 10g of the photocurable resin composition obtained in the examples and comparative examples, 0.03g of spacer particles ("Micropearl SP-210" manufactured by Sekisui Chemical Co., Ltd.) with a diameter of 10μm was added and uniformly dispersed using a stirring mixer ("AR-250" manufactured by THINKY Co., Ltd.). After coating the photocurable resin composition dispersed with the spacer particles on a glass substrate A (a product obtained by washing a glass surface of 50mm long, 25mm wide, and 0.7mm thick with acetone and then drying), a glass substrate B (a product obtained by immersing a glass of 5mm long, 5mm wide, and 0.7mm thick in acetone, washing it, and drying it) was attached, and pressurized to make the thickness uniform. Next, irradiation was performed using a UV-LED irradiation device at 3000mJ / cm 2 The photocurable resin composition was cured by ultraviolet light of a wavelength of 365 nm, thereby bonding glass substrate A and glass substrate B. The shear bonding strength between glass substrate A and glass substrate B was measured using a chip shear tester (manufactured by DAGE, "BOND TESTER 4000") at 23°C and a shear rate of 200 μm / sec.
[0138] Adhesion was evaluated by indicating a shear adhesive force of 200 N or more as “○”, a shear adhesive force of less than 200 N and 100 N or more as “△”, and a shear adhesive force of less than 100 N as “×”.
[0139] (Barrier properties)
[0140] The following Ca-TEST was performed on each of the photocurable resin compositions obtained in Examples and Comparative Examples.
[0141] First, 0.03 g of spacer particles (Micropearl SP-210 manufactured by Sekisui Chemical Co., Ltd.) with a diameter of 10 μm was added to 10 g of each photocurable resin composition obtained in the examples and comparative examples, and the mixture was uniformly dispersed using a stirring mixer (AR-250 manufactured by THINKY Co., Ltd.). Next, the photocurable resin composition with the spacer particles dispersed therein was applied to the surface of a glass substrate.
[0142] Next, a mask having a plurality of 2 mm × 2 mm openings was placed on another glass substrate of 30 mm × 30 mm in size, and Ca was deposited using a vacuum deposition machine. The deposition conditions were as follows: the pressure inside the deposition chamber of the vacuum deposition machine was reduced to 2 × 10 - 3 Pa, The evaporation rate of the film is Move the Ca-deposited glass substrate into a glove box that is managed to maintain a dew point (above -60°C), and bond the glass substrate coated with a photocurable resin composition on the surface to the Ca-deposited pattern of the glass substrate deposited with Ca via the photocurable resin composition. At this time, align the positions so that the deposited Ca is present at positions 2mm, 4mm, and 6mm from the end face of the glass substrate. After applying pressure to make the thickness of the photocurable resin composition layer uniform, irradiate with 3000mJ / cm 2 The photocurable resin composition was cured by ultraviolet rays of 365 nm, thereby producing a Ca-TEST substrate.
[0143] The obtained Ca-TEST substrate was exposed to high temperature and high humidity conditions of 85°C and 85%RH, and the water penetration distance per hour from the end surface of the glass substrate to the layer of the cured product of the photocurable resin composition sandwiched between the two glass substrates was observed based on the disappearance of Ca. As a result, the case where the time until the water penetration distance reached 6 mm was 1000 hours or more was marked as "○", the case where the time was 500 hours or more and less than 1000 hours was marked as "△", and the case where the time was less than 500 hours was marked as "×", and the barrier property was evaluated.
[0144] In addition, since the photocurable resin composition obtained in Comparative Example 11 peeled off the glass substrate in Ca-TEST, the barrier property could not be evaluated.
[0145] [Table 1]
[0146]
[0147] [Table 2]
[0148]
[0149] [Table 3]
[0150]
[0151] Industrial Applicability
[0152] According to the present invention, a photocurable resin composition having excellent storage stability, coating properties, adhesion and barrier properties can be provided. In addition, according to the present invention, a sealant for an organic EL display element and a sealant for a quantum dot device comprising the photocurable resin composition, an organic EL display element manufactured using the sealant for an organic EL display element, and a quantum dot device manufactured using the sealant for a quantum dot device can be provided.
Claims
1. A sealant for an organic EL display element, characterized in that: It contains a photocurable resin composition, The photocurable resin composition comprises: a polymer having a repeating unit represented by the following formula (1) in the main chain and a weight average molecular weight of 5000 to 100000; a monomer having an alicyclic skeleton and a methacryloyl group; a photoradical polymerization initiator; a water-absorbing filler; and other fillers other than the water-absorbing filler. The photocurable resin composition does not contain a solvent, The monomer having an alicyclic skeleton and a methacryloyl group comprises dicyclopentadiene dimethanol dimethacrylate, The water-absorbing filler comprises an oxide of an alkaline earth metal or a molecular sieve, The content of the monomer having an alicyclic skeleton and a methacryloyl group is 30 parts by weight or more and 70 parts by weight or less, and the content of the water-absorbing filler is 10 parts by weight or more and 200 parts by weight or less, based on 100 parts by weight of the total of the polymer having a repeating unit represented by the following formula (1) in the main chain and a weight average molecular weight of 5,000 or more and 100,000 or less and the monomer having an alicyclic skeleton and a methacryloyl group. The photocurable resin composition has a viscosity of 1 Pa·s or more and 1000 Pa·s or less as measured by an E-type viscometer at 25° C. and 2.5 rpm, The sealant for an organic EL display element is used to form a sealing wall around a laminate having an organic light-emitting material layer in a barrier filler seal. 。 2. The sealing agent for an organic EL display element according to claim 1, wherein The water-absorbing filler has an average primary particle size of 0.5 μm or more and 5 μm or less, and a specific gravity of 1.5 g / cm 3 Above and 3.3g / cm 3 the following.
3. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The water-absorbing filler is calcium oxide.
4. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The water-absorbing filler is magnesium oxide.
5. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The photocurable resin composition contains talc and / or silica as the other filler.
6. The sealing agent for an organic EL display element according to claim 1 or 2, wherein The photocurable resin composition further contains a tackifier. The photocurable resin composition contains 1 part by weight or more and 15 parts by weight or less of the tackifier based on 100 parts by weight of the total of the polymer having a repeating unit represented by formula (1) in the main chain and a weight average molecular weight of 5,000 to 100,000 and the monomer having an alicyclic skeleton and a methacryloyl group.
7. An organic EL display element produced by using the sealing agent for an organic EL display element according to claim 1, 2, 3, 4, 5 or 6.
Citation Information
Patent Citations
Polymeric agent for releasing 5-aminosalicylic acid or its derivatives into the gastrointestinal tract, pharmaceutical formulation comprising said agent,method of its preparation and method of preparing said formulation
EP0013000A2
Organic el display and manufacturing method of organic el display
JP2007059094A
Adhesive encapsulation composition and electronic device made using the same
JP2011526629A
Wavelength conversion sheet and backlight unit
WO2015037733A1
Photocurable elastomer composition, seal material, gasket for hard disk drive, hard disk drive and device
CN104968690A